Surgical and audiological outcome of canal wall down mastoidectomy in Sub Himalayan region: our experience - Thakur, Kuldeep; Ahluwalia, Ajay; Gupta, Vikas Deep (International Journal of Research in Medical Sciences, 2017)
Background: Pre-operative and post-operative hearing status and status of mastoid cavity were compared in patients undergoing canal wall down mastoidectomy (CWDM) with tympanoplasty. Methods: Forty-three patients who underwent surgery and completed their follow up post-surgery were included in the study. Nineteen patients underwent CWDM with type III tympanoplasty with PORP, 7 patients underwent CWDM with type III tympanoplasty without PORP and 17 patients underwent CWDM with type IV tympanoplasty with TORP. Results: Among enrolled patients, 21 patients were females and 22 patients were male. Right ear (29) was commonly involved than left ear (14). Hearing loss was predominant symptom followed by recurrent ear discharge and other symptoms. Patients underwent three types of surgeries, type III tympanoplasty with PORP (19/43), type III tympanoplasty without PORP (7/43) and type IV tympanoplasty with TORP (17/43) by using Teflon prosthesis. Conclusions: Thirty seven percent (16/43) of patients had hearing threshold <25 dB post-surgery with maximum improvement in group A 47% (9/19). Forty seven percent (20/43) patients had hearing threshold between 26-40 dB with maximum improvement in group B 43% (3/7). Twelve percent (5/43) patients had hearing threshold between 41-60dB with almost equal improvement in all three groups. Five percent (2/43) of patients had >60dB hearing threshold, all belonging to group C. Anatomical results were assessed by examining the mastoid cavity showing 95%, 72%, 70% patients in group A, B and C had well epithelialized cavity.